2021
DOI: 10.1136/bmjopen-2021-052755
|View full text |Cite
|
Sign up to set email alerts
|

Risk of 30-day hospital readmission associated with medical conditions and drug regimens of polymedicated, older inpatients discharged home: a registry-based cohort study

Abstract: ObjectivesThe present study analysed 4 years of a hospital register (2015–2018) to determine the risk of 30-day hospital readmission associated with the medical conditions and drug regimens of polymedicated, older inpatients discharged home.DesignRegistry-based cohort study.SettingValais Hospital—a public general hospital centre in the French-speaking part of Switzerland.ParticipantsWe explored the electronic records of 20 422 inpatient stays by polymedicated, home-dwelling older adults held in the hospital’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 78 publications
(138 reference statements)
2
20
2
Order By: Relevance
“…In concordance with previous studies, the number of comorbidities directly correlates with the frequency of 30-day readmission after hospital discharge [20] [21]. Particularly such conditions as fluid and electrolyte disorders, cardiac arrhythmia, hypertension, congestive heart failure, pulmonary circulation disorders, depression, and malignant cancer.…”
Section: Discussionsupporting
confidence: 88%
“…In concordance with previous studies, the number of comorbidities directly correlates with the frequency of 30-day readmission after hospital discharge [20] [21]. Particularly such conditions as fluid and electrolyte disorders, cardiac arrhythmia, hypertension, congestive heart failure, pulmonary circulation disorders, depression, and malignant cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are also consistent with those of multiple studies that have identified polypharmacy as a risk factor for hospitalization, longer length of hospital stay, and mortality risk in older patients. [22][23][24] The lower readmission rate of 10.2% overall likely reflects the dramatic change in hospitalization and rehospitalization during the COVID-19 pandemic. The patterns of hospital readmission changed after COVID-19 became an important cause of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Without preventative measures, MRPs can lead to physical and cognitive decline, exacerbated chronic medical conditions, rehospitalisations, avoidable health costs [9][10][11], and, sometimes, unplanned institutionalisation [12]. Nurses can play a crucial preventative role in ensuring safe medication management for polymedicated home-dwelling older adults [13,14].…”
Section: Introductionmentioning
confidence: 99%